Review on inorganic pollutants in stormwater runoff of non-metal roofs - Degenhart, Julia; Helmreich, Brigitte (Frontiers in Environmental Chemistry, 2022)
Metal roofs have always been in the focus of stormwater runoff contamination. However, other roofing materials are also suspected of releasing metals and other inorganic substances with stormwater runoff. Hence, this review focuses on the impact of commonly used non-metal roofs - vegetated and non-vegetated - on stormwater runoff quality. Results from 42 studies were compiled and assessed to gain an overview of substances in runoff from nine roofing types with a special focus on green roofs. Concentrations of 27 substances including nutrients, heavy metals, and other inorganic substances were compared. Results show that the nine roof types that were assessed can be a potential source for inorganic substances in the runoff. Threshold values for groundwater protection are exceeded especially for PO43-, Cu, Pb, and Zn for some roofing materials. As the concentrations vary strongly for different parameters, no roofing material can be identified as clearly superior or inferior to the others. Gravel roofs act as a sink for NH4+ and can retain some heavy metals. Elevated heavy metal concentrations were found in runoff from wood shingle roofs treated with preservative chemicals and in runoff from most roofing types usually due to the used gutter materials. Green roof runoff shows increased concentrations of Ptot, PO43-, Na, K, Ca, and Mg. The concentrations depend strongly on the green roof age, the growth substrate, and applied fertilizers. In addition to the roofing materials, external factors dependent on the location (rural or urban site) influence the runoff quality. Runoff from the analyzed roofs must be seen as a diffuse source of environmental pollution and requires appropriate treatment before it is released into the environment or used for further applications. Overall, there are only a few studies on the topic so it is not possible to make statistically significant statements. More serious in-depth studies are urgently needed.